Spatiotemporal Dynamic Regulation of Organelles During Meiotic Development, Insights From Fungi - Hernández-Sánchez, Fernando; Peraza-Reyes, Leonardo (Frontiers in Cell and Developmental Biology, 2022)
Eukaryotic cell development involves precise regulation of organelle activity and dynamics, which adapt the cell architecture and metabolism to the changing developmental requirements. Research in various fungal model organisms has disclosed that meiotic development involves precise spatiotemporal regulation of the formation and dynamics of distinct intracellular membrane compartments, including peroxisomes, mitochondria and distinct domains of the endoplasmic reticulum, comprising its peripheral domains and the nuclear envelope. This developmental regulation implicates changes in the constitution and dynamics of these organelles, which modulate their structure, abundance and distribution. Furthermore, selective degradation systems allow timely organelle removal at defined meiotic stages, and regulated interactions between membrane compartments support meiotic-regulated organelle dynamics. This dynamic organelle remodeling is implicated in conducting organelle segregation during meiotic differentiation, and defines quality control regulatory systems safeguarding the inheritance of functional membrane compartments, promoting meiotic cell rejuvenation. Moreover, organelle remodeling is important for proper activity of the cytoskeletal system conducting meiotic nucleus segregation, as well as for meiotic differentiation. The orchestrated regulation of organelle dynamics has a determinant contribution in the formation of the renewed genetically-diverse offspring of meiosis.